Prognostic significance of preoperative peripheral blood neutrophil to lymphocyte ratio (NLR) in lung sarcomatoid carcinoma - Liu, Jun; Li, Shuman; Liu, Hao; Chen, Keming; Chen, Renliu; Xiao, Yongbo; Zhang, Xinke; Chen, Jiewei (Translational Cancer Research, 2019)
Background: The present study aimed to evaluate the prognostic value of the neutrophil to lymphocyte ratio (NLR) in patients with lung sarcomatoid carcinoma (LSC). Methods: We retrospectively analyzed the clinicopathological parameters of 100 cases of LSC in the Sun Yat-sen University Cancer Center. Receiver operator characteristics curve analysis was performed to define the cutoff point for the preoperative peripheral blood NLR. The relationship between NLR and the clinicopathological parameters of patients with LSC was estimated using χ2 analysis. Univariate and multivariate statistical analyses were carried out to evaluate the impact of preoperative blood NLR on postoperative survival of patients with LSC. Results: The analyses revealed that the preoperative peripheral blood NLR was significantly associated with tumor size, pN stage, and clinical stage (P